Molecular mechanisms involved in Plasmodium gametocytogenesis - Scovino, Aline Miranda; Oliveira-da-Silva, Rafaella Stéfany; Almeida-da-Silva, Joyce; Mendes, Karolynne Dantas; da Silva-Junior, Elias Barbosa; Decote-Ricardo, Debora; Freire-de-Lima, Leonardo; Freire-de-Lima, Celio Geraldo; Totino, Paulo Renato Rivas; Morrot, Alexandre (Frontiers in Microbiology, 2026)
Malaria, a disease caused by protozoa of the genus Plasmodium, remains a major challenge for global public health. The persistence of disease transmission to the mosquito vector depends on the differentiation of asexual blood-stage parasites into gametocytes, a process known as gametocytogenesis. Interrupting this stage of the parasite’s life cycle represents a critical strategy for malaria control and eventual eradication. This review aims to consolidate recent advances in the understanding of the complex molecular mechanisms regulating gametocytogenesis in Plasmodium, with a particular focus on P. falciparum. Sexual differentiation is modulated by various factors, including environmental stressors such as the depletion of lysophosphatidylcholine (LysoPC), and is orchestrated through a sophisticated regulatory network. At the transcriptional level, the AP2-G transcription factor functions as a master switch, whose expression is tightly regulated by epigenetic mechanisms, including histone H3K9 trimethylation (H3K9me3) as well as the activity of both heterochromatin protein 1 (HP1) and gametocyte development protein 1 (GDV1). Following commitment, post-transcriptional regulation plays a critical role in further differentiation, including transcript stabilization by RNA-binding proteins such as PfPuf1 and PfPuf2, along with epitranscriptomic modifications such as mRNA methylation (m5C and m6A), which modulate gene expression. A comprehensive understanding of these interconnected regulatory pathways is essential for the identification of novel therapeutic targets and the development of effective transmission-blocking vaccines.